Turf algae-mediated coral damage in coastal reefs of Belize, Central America - Wild,Christian; Jantzen,Carin; Kremb,Stephan Georg (PeerJ, 2014)
Many coral reefs in the Caribbean experienced substantial changes in their benthic community composition during the last decades. This often resulted in phase shifts from scleractinian coral dominance to that by other benthic invertebrate or algae. However, knowledge about how the related role of coral-algae contacts may negatively affect corals is scarce. Therefore, benthic community composition, abundance of algae grazers, and the abundance and character of coral-algae contacts were assessed in situ at 13 Belizean reef sites distributed along a distance gradient to the Belizean mainland (12–70 km): Mesoamerican Barrier Reef (inshore), Turneffe Atoll (inner and outer midshore), and Lighthouse Reef (offshore). In situ surveys revealed significantly higher benthic cover by scleractinian corals at the remote Lighthouse Reef (26–29%) when compared to the other sites (4–19%). The abundance of herbivorous fish and the sea urchin Diadema antillarum significantly increased towards the offshore reef sites, while the occurrence of direct coral-algae contacts consequently increased significantly with decreasing distance to shore. About 60% of these algae contacts were harmful (exhibiting coral tissue damage, pigmentation change, or overgrowth) for corals (mainly genera Orbicella and Agaricia), particularly when filamentous turf algae were involved. These findings provide support to the hypothesis that (turf) algae-mediated coral damage occurs in Belizean coastal, near-shore coral reefs.
Keywords: Coral reef ecology; Phase shift; Coastal influence; Coral algae contacts